A composite binder phase toughened (ti,m)c based cermet and a method of making the same
Patent Information
- Application Number
- CN202310568391.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-19
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-05-19
AI Technical Summary
In the prior art, commercially available high-entropy alloys have poor wettability on (Ti,M)C ceramic particles, resulting in insufficient strength of the prepared metal ceramics, and the traditional binder phase has insufficient toughness and hardness.
Using nickel and a high-entropy alloy as composite binders, (Ti,M)C-based cermets with a composite binder phase composed of a (Ti,M)C solid solution hard phase, a ring phase, a nickel binder phase, and a high-entropy alloy binder phase were prepared through mechanical alloying and vacuum sintering processes. This ensured good wettability and comprehensive mechanical properties between the binder phase and the ceramic particles.
(Ti,M)C-based cermets with fine grains and uniform microstructure were prepared, which significantly improved high-temperature strength and had excellent comprehensive mechanical properties. Moreover, the preparation process was simple and the cost was low.
Smart Images

Figure CN116752022B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite materials, specifically to a (Ti,M)C-based cermet with a composite binder phase and its preparation method. Background Technology
[0002] (Ti,M)C-based cermets possess advantages such as high hardness, high wear resistance, high-temperature red hardness, and oxidation resistance, making them promising for applications in wear-resistant parts and machining molds. For cermets, a suitable binder phase can not only dissolve the hard phase to a certain extent and inhibit abnormal grain growth, but also fully wet the hard phase, improving density and the bonding strength at the two-phase interface. Traditional binder phases often use Co, Ni, and Fe, which offer good toughness but insufficient strength and hardness.
[0003] High-entropy alloys (HE A) are a new type of alloy formed by alloying five or more main elements in equiatomic or near-equiatomic ratios. Due to their four major thermodynamic and kinetic effects—high-entropy effect, lattice distortion effect, hysteresis diffusion effect, and cocktail effect—they readily form structurally stable solid solution phases, reducing the number of interfaces and exhibiting superior properties compared to traditional alloys. (Ti,M)C composite ceramics prepared using high-entropy alloys (HE A) as the binder phase demonstrate excellent hardness and fracture toughness. However, commercially available high-entropy alloys (HE A) exhibit poor wettability on (Ti,M)C ceramic particles, resulting in insufficient strength in the prepared cermets. Summary of the Invention
[0004] The purpose of this invention is to address the shortcomings of the aforementioned background technology by providing a (Ti,M)C-based cermet with a composite binder phase and its preparation method. Using nickel and a high-entropy alloy as the composite binder phase, the excellent comprehensive properties of the high-entropy alloy can be utilized to achieve effects such as binder phase strengthening and grain refinement, while also ensuring good wettability between the binder phase and ceramic particles. This results in the preparation of (Ti,M)C-based cermets with fine grains, uniform structure, and excellent comprehensive mechanical properties, especially with significantly improved high-temperature strength. Furthermore, the preparation process is simple and cost-effective.
[0005] To achieve the above objectives, the present invention mainly provides the following technical solutions: A (Ti,M)C-based cermet with a composite binder phase is characterized by being composed of a (Ti,M)C solid solution hard phase and a nickel and high-entropy alloy composite binder phase. The microstructure, from the inside out, consists of a hard core phase, a ring phase, a nickel binder phase, a transition layer, and a high-entropy alloy binder phase.
[0006] Furthermore, in the (Ti,M)C solid solution hard phase, M is at least one of the metals W, Cr, Ta, Mo, Nb, Zr, V, and Hf, and the average grain size of the (Ti,M)C solid solution hard phase is 0.5-15 μm.
[0007] Furthermore, the high-entropy alloy is composed of Ni and at least three elements selected from Co, Cr, Fe, Mo, Zr, Ti, Al, Y, Si, Mn, and W, with the atomic fraction of Ni and the selected at least three elements being 2%-40%.
[0008] Furthermore, the preparation process of the aforementioned composite binder-strengthened metal-ceramic is as follows: 1) Prepare high-entropy alloy mixture: Weigh and mix nickel and at least three elements from cobalt, chromium, iron, molybdenum, zirconium, titanium, aluminum, yttrium, silicon, manganese and tungsten according to the composition and mass fraction of the designed high-entropy alloy. The atomic fraction of nickel and the other three elements is 2%-40%.
[0009] 2) Mechanical alloying: The prepared mixed powder is mechanically alloyed on a planetary ball mill, wherein the ball-to-powder ratio is 10:1 to 30:1, the ball milling speed is 200 to 500 rpm, the ball milling time is 12 to 90 h, and Ar protection is used during the ball milling process; 3) Prepare composite ceramic mixture: The toughened metal-ceramic with the composite binder phase was prepared according to the following composition (mass fraction): (Ti,M)C: 48-80%; Mo: 3-10%; C:0-2%; Composite binder phase: 15%~40%, wherein the mass ratio of nickel powder to the high-entropy alloy powder obtained in step 2 is 1:1-5:1; 4) Ball milling and mixing: The prepared ceramic mixture is placed on an all-around planetary ball mill for ball milling, with a ball-to-material ratio of 5:1 to 10:1, a ball milling speed of 150 to 450 rpm, a ball milling time of 2 to 60 hours, and ethanol as the ball milling medium. 5) Drying and sieving: Dry the ball-milled mixed powder in a vacuum drying oven at a temperature of 70~110℃, and then sieve the dried powder through a 100~200 mesh screen. 6) Molding: After the dried powder is sieved, it is molded. The pressing pressure is 200~400MPa and the holding time is 10~120s. 7) Sintering: The molded blank from step 6) is sintered in a vacuum sintering furnace with a vacuum degree of not less than 1×10⁻⁶. -1 Pa, sintering temperature is 1400~1550℃, holding time is 1-5h.
[0010] The present invention has the following technical effects: 1) Composite binder phases can balance wettability and optimize binder phase characteristics, resulting in metal ceramics with better overall performance.
[0011] 2) The preparation process described in this invention is simple, requiring no complex processes such as hot pressing or gas pressing, and the composition is simple and the cost is low.
[0012] 3) The flexural strength of the prepared cermet is not less than 1950 MPa, and the fracture toughness is not less than 10.5 MPa·m. 1 / 2 The Rockwell hardness is not less than 90.0 HRA.
[0013] The composite binder phase-strengthened (Ti,M)C-based cermets of the present invention use nickel and high-entropy alloy as composite binder phases. The excellent comprehensive properties of high-entropy alloys can be used to achieve effects such as binder phase strengthening and grain refinement, while also ensuring good wettability between the binder phase and ceramic particles. This results in the preparation of (Ti,M)C-based cermets with fine grains, uniform structure and excellent comprehensive mechanical properties. Attached Figure Description
[0014] Figure 1 This is a SEM-BSE microstructure image of the metal ceramic prepared in Example 5 of the present invention. Detailed Implementation
[0015] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments to facilitate a clear understanding of the present invention, but these descriptions do not constitute a limitation on the present invention.
[0016] Example 1: Step 1: Prepare the high-entropy alloy mixture: Weigh and mix the Co, Cr, Fe, Ni and Mo metal powders according to the designed composition and mass fraction of the high-entropy alloy, wherein the atomic fraction of Co is 20%, the atomic fraction of Ni is 40%, the atomic fractions of Cr and Fe are both 19%, and the atomic fraction of Mo is 2%.
[0017] Step 2: Mechanical alloying: The prepared mixed powder is mechanically alloyed on a planetary ball mill with a ball-to-powder ratio of 10:1, a ball milling speed of 500 rpm, and a ball milling time of 90 h. Ar protection is used during the ball milling process to obtain high-entropy alloy powder. Step 3: Prepare the composite ceramic mixture: The toughened metal-ceramic with the composite binder phase was prepared according to the following composition (mass fraction): (Ti,W)C: 48%, Mo: 10%; C: 2%; Composite binder phase: 40%, wherein the mass ratio of nickel powder to the high-entropy alloy powder obtained in step 2 is 5:1; Step 4: Ball milling and mixing: The prepared composite ceramic powder is ball milled in an all-around planetary ball mill with a ball-to-material ratio of 10:1, a ball milling speed of 450 rpm, a ball milling time of 60 h, and ethanol as the ball milling medium. Step 5: Drying and sieving: Dry the ball-milled mixed powder in a vacuum drying oven at 70 ℃, and then sieve the dried powder through a 200-mesh sieve. Step 6: Compression molding: After the dried powder is sieved, it is compression molded with a pressing pressure of 400MPa and a holding time of 120s. Step 7: Vacuum sintering: The pressed billet is sintered in a vacuum sintering furnace with a vacuum degree of not less than 1×10⁻⁶. -1 Pa, sintering temperature is 1400℃, holding time is 5h.
[0018] The properties of the cermet prepared in Example 1 are shown in Table 1.
[0019] Example 2: Step 1: Prepare the high-entropy alloy mixture: Weigh and mix the Co, Cr, Fe, Ni and Ti metal powders according to the designed composition and mass fraction of the high-entropy alloy, wherein the atomic fraction of Ti is 40%, and the atomic fractions of Co, Cr, Fe and Ni are all 15%.
[0020] Step 2: Mechanical alloying: The prepared mixed powder is mechanically alloyed on a planetary ball mill with a ball-to-powder ratio of 10:1, a ball milling speed of 200 rpm, and a ball milling time of 12 h. Ar protection is used during the ball milling process to obtain high-entropy alloy powder. Step 3: Prepare the composite ceramic mixture: The toughened metal-ceramic with the composite binder phase was prepared according to the following composition (mass fraction): (Ti,W)C: 48%; Mo: 10%; C: 2%; Composite binder phase: 40%, wherein the mass ratio of nickel powder to the high-entropy alloy powder obtained in step 2 is 1:1; Step 4: Ball milling and mixing: The prepared composite ceramic powder is ball milled in an all-around planetary ball mill with a ball-to-material ratio of 5:1, a ball milling speed of 150 rpm, a ball milling time of 2 hours, and ethanol as the ball milling medium. Step 5: Drying and sieving: Dry the ball-milled mixed powder in a vacuum drying oven at 70 ℃, and then sieve the dried powder through a 100-mesh sieve. Step 6: Compression molding: After the dried powder is sieved, it is compression molded with a pressing pressure of 200MPa and a holding time of 10s. Step 7: Vacuum sintering: The pressed billet is sintered in a vacuum sintering furnace with a vacuum degree of not less than 1×10⁻⁶.-1 Pa, sintering temperature is 1420℃, holding time is 3h.
[0021] The properties of the cermet prepared in Example 2 are shown in Table 1.
[0022] Example 3: Step 1: Prepare the high-entropy alloy mixture: Weigh and mix the Co, Cr, Si, Ni and Mo metal powders according to the designed composition and mass fraction of the high-entropy alloy, with each element having an atomic fraction of 20%.
[0023] Step 2: Mechanical alloying: The prepared mixed powder is mechanically alloyed on a planetary ball mill with a ball-to-powder ratio of 20:1, a ball milling speed of 300 rpm, and a ball milling time of 24 h. Ar protection is used during the ball milling process to obtain high-entropy alloy powder. Step 3: Prepare the composite ceramic mixture: The toughened metal-ceramic with the composite binder phase was prepared according to the following composition (mass fraction): (Ti,W)C: 80%; Mo: 3%; C: 2%; Composite binder phase: 15%, wherein the mass ratio of nickel powder to the high-entropy alloy powder obtained in step 2 is 5:1; Step 4: Ball milling and mixing: The prepared composite ceramic powder is ball milled in an all-around planetary ball mill with a ball-to-material ratio of 7:1, a ball milling speed of 350 rpm, a ball milling time of 48 h, and ethanol as the ball milling medium. Step 5: Drying and sieving: Dry the ball-milled mixed powder in a vacuum drying oven at 89°C, and then sieve the dried powder through a 100-mesh sieve. Step 6: Compression molding: After the dried powder is sieved, it is compression molded with a pressing pressure of 300MPa and a holding time of 60s. Step 7: Vacuum sintering: The pressed billet is sintered in a vacuum sintering furnace with a vacuum degree of not less than 1×10⁻⁶. -1 Pa, sintering temperature is 1500℃, holding time is 2h.
[0024] The properties of the cermet prepared in Example 3 are shown in Table 1.
[0025] Example 4: Step 1: Prepare the high-entropy alloy mixture: Weigh and mix the Co, Cr, Fe, Ni and Al metal powders according to the designed composition and mass fraction of the high-entropy alloy, with each element having an atomic fraction of 20%.
[0026] Step 2: Mechanical alloying: The prepared mixed powder is mechanically alloyed on a planetary ball mill with a ball-to-powder ratio of 30:1, a ball milling speed of 300 rpm, and a ball milling time of 48 h. Ar protection is used during the ball milling process to obtain high-entropy alloy powder. Step 3: Prepare the composite ceramic mixture: The toughened metal-ceramic with the composite binder phase was prepared according to the following composition (mass fraction): (Ti,W)C: 80%; Mo: 3%; C: 2%; Composite binder phase: 15%, wherein the mass ratio of nickel powder to the high-entropy alloy powder obtained in step 2 is 1:1; Step 4: Ball milling and mixing: The prepared composite ceramic powder is ball milled in an all-around planetary ball mill with a ball-to-material ratio of 10:1, a ball milling speed of 300 rpm, a ball milling time of 24 h, and ethanol as the ball milling medium. Step 5: Drying and sieving: Dry the ball-milled mixed powder in a vacuum drying oven at 110°C, and then sieve the dried powder through a 100-mesh sieve. Step 6: Compression molding: After the dried powder is sieved, it is compression molded with a pressing pressure of 300MPa and a holding time of 60s. Step 7: Vacuum sintering: The pressed billet is sintered in a vacuum sintering furnace with a vacuum degree of not less than 1×10⁻⁶. -1 Pa, sintering temperature is 1550℃, holding time is 1h.
[0027] The properties of the cermet prepared in Example 4 are shown in Table 1.
[0028] Example 5: Step 1: Prepare the high-entropy alloy mixture: Weigh and mix the Co, Cr, Fe, Ni and Mo metal powders according to the designed composition and mass fraction of the high-entropy alloy, with each element having an atomic fraction of 20%.
[0029] Step 2: Mechanical alloying: The prepared mixed powder is mechanically alloyed on a planetary ball mill with a ball-to-powder ratio of 20:1, a ball milling speed of 300 rpm, and a ball milling time of 48 h. Ar protection is used during the ball milling process to obtain high-entropy alloy powder. Step 3: Prepare the composite ceramic mixture: The toughened metal-ceramic with the composite binder phase was prepared according to the following composition (mass fraction): (Ti,W)C: 61%; Mo: 8%; C: 1%; Composite binder phase: 30%, wherein the mass ratio of nickel powder to the high-entropy alloy powder obtained in step 2 is 3:1; Step 4: Ball milling and mixing: The prepared composite ceramic powder is ball milled in an all-around planetary ball mill with a ball-to-material ratio of 7:1, a ball milling speed of 220 rpm, a ball milling time of 48 h, and ethanol as the ball milling medium. Step 5: Drying and sieving: Dry the ball-milled mixed powder in a vacuum drying oven at 90°C, and then sieve the dried powder through a 100-mesh sieve. Step 6: Compression molding: After the dried powder is sieved, it is compression molded with a pressing pressure of 300MPa and a holding time of 60s. Step 7: Vacuum sintering: The pressed billet is sintered in a vacuum sintering furnace with a vacuum degree of not less than 1×10⁻⁶. -1 Pa, sintering temperature is 1470℃, holding time is 3h.
[0030] The properties of the cermets prepared in Example 5 are shown in Table 1. The SEM-BSE microstructure of the prepared cermets is shown in the figure. Figure 1 As shown.
[0031] Comparative Example 1: Step 1: Prepare the composite ceramic mixture: The toughened metal-ceramic with the composite binder phase was prepared according to the following composition (mass fraction): (Ti,W)C: 61%; Mo: 8%; C: 1%; Ni: 30%; Step 4: Ball milling and mixing: The prepared mixed powder is ball milled in an all-around planetary ball mill with a ball-to-powder ratio of 7:1, a ball milling speed of 220 rpm, a ball milling time of 48 h, and ethanol as the ball milling medium. Step 5: Drying and sieving: Dry the ball-milled mixed powder in a vacuum drying oven at 90°C, and then sieve the dried powder through a 100-mesh sieve. Step 6: Compression molding: After the dried powder is sieved, it is compression molded with a pressing pressure of 300MPa and a holding time of 60s. Step 7: Vacuum sintering: The pressed billet is sintered in a vacuum sintering furnace with a vacuum degree of not less than 1×10⁻⁶. -1 Pa, sintering temperature is 1470℃, holding time is 3h.
[0032] The properties of the cermet prepared in Comparative Example 1 are shown in Table 1.
[0033] Table 1 Mechanical properties of each embodiment and comparative example Compared with the comparative example, Example 5 showed the same room temperature strength, but a significant increase in high temperature strength, as well as increased hardness and toughness.
Claims
1. A (Ti,M)C-based cermet with a composite binder phase for enhanced toughness, characterized in that: The cermet is composed of a (Ti,M)C solid solution hard phase and a nickel and high-entropy alloy composite binder phase. Its microstructure, from the inside out, consists of a hard core phase, a ring-shaped phase, a nickel binder phase, a transition layer, and a high-entropy alloy binder phase. The flexural strength of the cermet is not less than 1950 MPa, and its fracture toughness is not less than 10.5 MPa·m. 1 / 2 The Rockwell hardness is not less than 90.0 HRA, and the bending strength at 800℃ is not less than 750 MPa; in the (Ti,M)C solid solution hard phase, M is W, and the high-entropy alloy is composed of Ni and at least three elements selected from Co, Cr, Fe, Mo, Zr, Ti, Al, Y, Si, Mn, and W, with the atomic fraction of Ni and the selected at least three elements being 2%-40%; The preparation method of the (Ti,M)C-based cermet with composite binder phase strengthening, with each ingredient expressed as a percentage by mass, includes the following steps: 1) Prepare high-entropy alloy mixture: Weigh and mix nickel and at least three elements selected from cobalt, chromium, iron, molybdenum, zirconium, titanium, aluminum, yttrium, silicon, manganese, and tungsten according to the composition and mass fraction of the designed high-entropy alloy. The atomic fraction of nickel and the selected at least three elements is 2%-40%. 2) Mechanical alloying: The high-entropy alloy mixture powder prepared in step 1) is mechanically alloyed on a planetary ball mill, wherein the ball-to-powder ratio is 10:1 to 30:1, the ball milling speed is 200 to 500 rpm, the ball milling time is 12 to 90 h, and Ar protection is used during the ball milling process to obtain high-entropy alloy powder. 3) Prepare composite ceramic mixture: (Ti,M)C: 48-80%, Mo: 3-10%, C: 0-2%, The composite adhesive phase comprises 15% to 40%, and is composed of nickel and high-entropy alloy, wherein the mass ratio of nickel powder to the high-entropy alloy powder obtained in step 2) is 1:1 to 5:
1. 4) Ball milling and mixing: The prepared composite ceramic mixture is placed on an all-around planetary ball mill for ball milling, wherein the ball-to-material ratio is 5:1 to 10:1, the ball milling speed is 150 to 450 rpm, the ball milling time is 2 to 60 hours, and the ball milling medium is ethanol. 5) Drying and sieving: Dry the ball-milled mixed powder in a vacuum drying oven at a temperature of 70~110℃, and then sieve the dried powder through a 100~200 mesh screen. 6) Compression molding: After sieving, compression molding is carried out with a pressing pressure of 200~400MPa and a holding time of 10~120s; 7) Sintering: The molded blank from step 6) is sintered in a vacuum sintering furnace with a vacuum degree of not less than 1×10⁻⁶. -1 Pa, sintering temperature is 1400~1550℃, holding time is 1-5h.
2. The (Ti,M)C-based cermet with composite binder phase reinforcement as described in claim 1, characterized in that, The average grain size of the hard phase in (Ti,M)C solid solution is 0.5-15 μm.
Citation Information
Patent Citations
Method for preparing TiC-based metal ceramic with high-entropy alloy binding phase
CN112680646A
